State of knowledge: Professional Education in situations of restriction of freedom (Práxis Educativa, 2019)
This work seeks to analyze the panorama of scientific productions in the stricto sensu graduate programs, regarding professional education in prison spaces. Focusing on professional education under the scope of resocialization, we proceeded to the survey of theses and dissertations on the subject, using as source the Brazilian Digital Library of Theses and Dissertations (Biblioteca Digital Brasileira de Teses e Dissertações – BDTD). We found that the issue of professional education in the prison system has been little explored, especially in doctoral courses. Thus, there is still much to be researched, especially considering the complexity of the issue, the vertiginous increase of incarcerations within the country in the last two decades and the emancipatory potential that the professional education presents for people in a situation of restriction of freedom. Keywords: State of knowledge. Professional education. Education for prisoners.